Being Bizzare: A New Composition Music | Being Bizzare: Sebuah Komposisi Musik Baru - I Nyoman Wiradarma Yoga; Hendra Santosa (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The purpose of creating the musical composition Being Bizzare is to raise a physiological phenomenon about schizophrenia, namely an acute stress condition.. Like the story of John in the film